The existence of the mixed race damnés : decolonialism, class, gender, race - Taylor-Garcia, Daphne V., 1973- (Global critical Caribbean thought, 2018)
This book explains the racial construction of mixed-race Latinxs in the Americas, centring an intersectional analysis in the theory of coloniality. It explores the first person experience with an analysis of semiotic structures and connects theory and history to action.